Corporatization and privatization of public services: origins and rise of a controversial concept - Phua, K. L. (Universiti Kebangsaan Malaysia, 2001)
The Malaysian government has been implementing its policy of corporatization and privatization of public services is traced back to the crisis of the welfare state in Britain and America and the influence of intellectuals and think tanks that favour free market policies and abhor government intervention in economic affairs. The growth in influence of this concept illustrates the impact that intellectuals can have when their ideas fall on the ears of sympathetic politicians and political movements under certain socioeconomic climates.